The whole sky - Henson, Heather (New York : Atheneum Books for Young Readers, 2017)
Twelve-year-old Sky, a horse whisperer like her father, must put her own troubles aside when a devastating sickness strikes the foals at the multimillion dollar horse farms where they work.
"A Caitlyn Dlouhy Book."
Includes bibliographical references (pages [241-245]).
A Junior Library Guild selection.
Keywords: Horses -- Juvenile fiction; Human-animal communication -- Juvenile fiction; Fathers and daughters -- Juvenile fiction; Veterinary medicine -- Juvenile fiction; Farm life -- Juvenile fiction; Grief -- Juvenile fiction; Irish Travellers (Nomadic people) -- Juvenile fiction; Horses -- Fiction; Human-animal communication -- Fiction; Fathers and daughters -- Fiction; Veterinary medicine -- Fiction; Horse farms -- Fiction; Fathers and daughters -- Fiction; JUVENILE FICTION / Social Issues / Death & Dying; Farm life -- Fiction; Veterinary medicine -- Fiction; Horses -- Fiction; Grief -- Fiction; JUVENILE FICTION / Animals / Horses; JUVENILE FICTION / Family / General (see also headings under Social Issues.)